Traceability of highly pathogenic avian influenza in dairy cattle production: economic impacts on milk transportation in Southwest Kansas - Zamora, Diana F. (My University, 2026)
This study examines the economic impact of the ongoing Highly Pathogenic Avian Influenza (HPAI) outbreak on the U.S. dairy industry, particularly in Southwest Kansas. The spread of diseases can significantly impact the economy, as demonstrated by previous pandemics, specifically COVID-19. The outbreak of the HPAI has provoked significant economic losses and increased the risk of sporadic human infections, highlighting the need for stricter monitoring and regulatory measures. The Kansas Department of Agriculture has implemented the Kansas Secure Milk Supply (KS SMS) Plan, which facilitates safe raw milk movement through enhanced surveillance, training, and biosecurity protocols. This research aims to evaluate the costs associated with traceability systems and the implementation of biosecurity measures in milk transportation. By analyzing direct government expenses and HPAI prevention initiatives, the study seeks to provide insights for stakeholders and regulatory agencies to improve traceability systems and ensure the safety of milk supply during an outbreak. The direct cost summary and scenario analysis show that although full implementation of the KS SMS Plan requires higher initial investment, it offers the greatest reduction in disease-spread risk and minimizes additional indirect costs to the government, ultimately supporting continuity of milk movement and strengthening overall emergency response capacity.
Keywords: Highly Pathogenic Avian Influenza (HPAI); Government cost analysis; Disease preparedness and response; Kansas Secure Milk Supply Plan (KS SMS Plan); Tracebility; Prevention programs